Creatine kinase, neuromuscular fatigue, and the contact codes of football: A systematic review and meta-analysis of pre- and post-match differences - Hagstrom, A. D.; Shorter, K. A. (European Journal of Sport Science, 2018)
Physiological or performance tests are routinely utilised to assess athletes` recovery. At present, the ideal tool to assess recovery remains unknown. Therefore, the aim of this systematic review was to examine the change in creatine kinase (CK) and neuromuscular function as measured via a countermovement jump (CMJ) following a match in the contact codes of football. A comprehensive search of databases was undertaken with RevMan (V 5.3) used for statistical analysis. Our results demonstrated that CK pre- versus post-match (standardised mean difference (SMD) = 0.90, 95% CI = 0.50 to 1.31, p < .0001), CK pre- versus 24 h post-match (SMD = 1.50, 95% CI = 1.12 to 1.88, p < .00001), and CK pre- versus 48 h post-match all increased significantly (SMD?= 0.90, 95% CI = 0.50 to 1.31, p < .0001), while CMJ peak power (PP) pre- versus post-match (SMD = -0.59, 95% CI = -1.12 to -0.06, p = .03), and pre- versus 24 h post-match (SMD = -0.80, 95% CI = -1.31 to -0.28, p = .002) decreased significantly. There was a significant relationship between the change in CK and the change in CMJ PP from immediately pre to immediately post (r = -0.924, p = .025), and between CMJ immediately following a match and 24 h CK change (r = -0.983, p = .017). In conclusion, CK levels increase and performance in the CMJ decreases following a match of a contact code of football. The identification of this relationship may allow coaching staff to implement a standalone measure of recovery.